2005
DOI: 10.1007/s10530-004-1663-x
|View full text |Cite
|
Sign up to set email alerts
|

Arrival rate of nonindigenous insect species into the United States through foreign trade

Abstract: Introductions of invasive nonindigenous species, and the ensuing negative ecological and economic consequences, have increased with expanding global trade. Quantifying the influx of nonindigenous plant pest species through foreign trade is required for national and international risk assessments, monitoring and conservation efforts, and evaluation of ecological factors that affect invasion success. Here we use statistically robust data collected at US ports of entry and border crossings to estimate arrival rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
200
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(213 citation statements)
references
References 29 publications
1
200
2
6
Order By: Relevance
“…Routine controls carried out in airports and harbours by quarantine services and monitoring by environmental or agricultural agencies are particularly informative in this respect (Work et al 2005). However, it is rarely possible to infer the routes of invasion with a high degree of precision by these direct methods.…”
Section: Discussionmentioning
confidence: 99%
“…Routine controls carried out in airports and harbours by quarantine services and monitoring by environmental or agricultural agencies are particularly informative in this respect (Work et al 2005). However, it is rarely possible to infer the routes of invasion with a high degree of precision by these direct methods.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing number of alien species introduced to different parts of the world, and their environmental and economic impacts (Pimentel et al 2005;Work et al 2005;Hulme et al 2009a, b;Roques et al 2009), understanding the mechanisms of biological invasions has become an important issue. Approximately 1,300 alien terrestrial invertebrate species are now established in Europe, representing one of the most numerous groups of organisms ).…”
Section: Introductionmentioning
confidence: 99%
“…seasonally). These strategies need to be informed by detailed national or regional level studies that consider both the number of organisms likely to be introduced from the donor region (see Bacon et al, 2012;Work et al, 2005) and the climatic similarity of the donor and recipient regions. However, the results of such studies must be carefully interpreted.…”
Section: Incorporating Establishment Debt Into Prioritised Inspectionmentioning
confidence: 99%
“…The assumptions made in this model may not hold in all instances and a variety of potentially important factors were not considered. For example, although it has been shown that observed alien species richness increases linearly with an increase in inspection effort (Work et al, 2005), various factors (e.g. packaging type) may affect the ease of inspections and consequently the likelihood of detecting an organism .…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation